The hollow crown - Wheeler, Jeff, 1971- (Wheeler, Jeff, 1971- Kingfountain series., 2017)
Following the downfall of a tyrant, years have passed in prosperity for the kingdom of Ceredigion. Now, as the time comes to celebrate the new king's nuptials, the specter of a new enemy emerges to destroy all that has been painstakingly built in those years. Tryneowy Kiskaddon has grown up learning military and diplomatic strategy from her father, one of the king's closest advisors. She feels her destiny lies in defending the kingdom as a knight, not as a Wizr as her parents have decided, though no lady of the realm has taken up the sword in a century. As she seeks to understand her own Fountain-blessed powers, she studies in the tradition of her mother while training in secret and closely following the realm's politics, alarmed by her mother's vision of an impending clash and a devastating future. But the pieces on fate's game board are in motion, and on the eve of battle, a threatening force irrevocably changes the future of the kingdom and her own. Does Trynne have what it takes to maneuver Ceredigion's key players into position and outsmart the kingdom's enemies--even those still concealed in shadow?